ESENSI SPIRIT PENDIDIKAN ISLAM DALAM KONSEP PEMIKIRAN PAULO FREIRE - Moh. Zaini (El-QUDWAH, 2014)
Oleh: Moh. Zaini Institut Keguruan dan Ilmu Pendidikan (IKIP) Budi Utomo Malang Email: pojur_zen@yahoo.com   Abstract In the view of Islam, Rosulullah have recounted: "Every child is born in the state of fitrah (the potential)..etc (HR. Al-Bukhari Muslims)., it indicates that actually the orientation of education is directed to the humanist process, by learning the human as the educated and dynamic subject with all its potential—not a passive subject, which is deceived by the external powers. However, people are active-autonomous-agents—who are able to determine their own movement— voters and the center of his own life. The orientation of this education system is in accordance with the education concept in Islam that has been taken from the definition of the term tarbiyah, ta'lim and ta'dib. By applying this system, it enables us to realize the humanist, critical and creative education with high moral standards. As it is said by Abbas r.a: "Be a good mannered scholar, with a deep knowledge and alim" (Imarah, 1979:62)